2015
DOI: 10.1074/jbc.m114.611327
|View full text |Cite
|
Sign up to set email alerts
|

Avian Influenza Virus Infection of Immortalized Human Respiratory Epithelial Cells Depends upon a Delicate Balance between Hemagglutinin Acid Stability and Endosomal pH

Abstract: Background:The mechanism of H5N1 pathogenesis in humans remains unclear. Results: SAEC-T clones were poorly susceptible to previously circulating avian influenza viruses but were completely susceptible to H5N1. Conclusion: Infectivity depends on a delicate balance between acid stability of viral hemagglutinin and endosomal pH in infected cells. Significance: These findings could explain why H5N1 is directly transmitted to humans from birds, resulting in serious illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 68 publications
5
47
0
Order By: Relevance
“…First, the kinetics of acidification and the levels of pH in the endosomal compartment may vary depending on host species, target tissue, cell type, and differentiation and metabolic state of the cell. A balance between endosomal pH in the cells and pH optimum of HA conformational transition was shown to affect the efficiency of viral infection (20,28,60). Differences in sensitivity of viruses to ammonium chloride during cell entry (Table 1) well illustrate this phenomenon.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…First, the kinetics of acidification and the levels of pH in the endosomal compartment may vary depending on host species, target tissue, cell type, and differentiation and metabolic state of the cell. A balance between endosomal pH in the cells and pH optimum of HA conformational transition was shown to affect the efficiency of viral infection (20,28,60). Differences in sensitivity of viruses to ammonium chloride during cell entry (Table 1) well illustrate this phenomenon.…”
Section: Discussionmentioning
confidence: 80%
“…Limited available data on fusion pH and stability of influenza viruses circulating in natural host species seem to indicate that human viruses fuse at a lower pH than avian and swine viruses (21,(26)(27)(28)(29)(30). However, different viral strains and distinctive assays were used by different authors, and pronounced subtype-and staindependent variation in the viral fusion activity was observed in these studies hampering solid conclusions.…”
mentioning
confidence: 64%
“…Collectively, these three assays indicated that the HAs of Mem-H1N1 and the two duck IAVs, mal-H1N1 and mal-H2N2, underwent conformational transition and mediated membrane fusion at a lower pH than the HAs of VN-H5N1 and Sh-H7N9 (Table 1). Thus, the receptor binding properties of the recombinant IAVs and their relative pH optima of membrane fusion well represented typical properties of IAVs from corresponding natural reservoirs (aquatic birds, gallinaceous poultry, and humans) (19)(20)(21)(22)(34)(35)(36)(37)(38)(39).…”
Section: Resultsmentioning
confidence: 85%
“…The pH optimum of HA-mediated fusion of avian and mammalian IAVs varies depending on the host species and the history of virus evolution, and our study, for the first time, demonstrates that this variation influences viral sensitivity to IFN and IFITMs. Among different IAVs, human viruses typically have the lowest fusion pH optimum (from 5.0 to 5.4), whereas swine viruses and viruses of gallinaceous poultry, including high-and low-pathogenic IAVs of the H5 and H7 subtypes, display relatively high fusion pH optima (5.6 to 6.0) (22,24,(34)(35)(36)(37)(38)(39). IAVs isolated from wild aquatic birds appear to be particularly variable with respect to the fusion pH optimum (from 5.0 to 6.0), although available data are limited (22-24, 37, 38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation